Analisis Penalaran Aljabar Siswa Kelas VIII Terhadap Materi Fungsi - Hafid, Nasya (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the algebraic reasoning abilities of 8th-grade students in understanding the concept of functions. Algebraic reasoning is examined based on three aspects from Kaput & Blanton’s theory: pattern generalization, multiple representations, and understanding algebraic structures. This qualitative descriptive research employed observation and interviews with two purposively selected students. The results show that students were able to identify numerical patterns and express function relationships using tables, graphs, and arrow diagrams. However, understanding of symbolic algebraic structures such as coefficients, variables, and constants remains informal. This study suggests the need for teachers to emphasize conceptual understanding and varied representations in algebra instruction.